2015
DOI: 10.1002/bit.25660
|View full text |Cite
|
Sign up to set email alerts
|

Activated air produced by shielded sliding discharge plasma mediates plasmid DNA delivery to mammalian cells

Abstract: Cold plasma is emerging as a potential method for medical applications. The current study assessed the efficacy of a novel cold plasma reactor based on shielded sliding discharge producing cathode-directed streamers generated in ambient air for the delivery of plasmid DNA. Experiments were performed with mouse melanoma cells (B16F10) and human keratinocyte cells (HaCaT) inoculated with plasmid DNA encoding luciferase. Quantitative results measured over a 72-h period displayed luciferase expression levels as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Chelsea et al . recently reported that using the plasma-activated air could deliver plasmid DNA into cells29, also suggesting that ROS are important for plasma transfection as the electric field is not involved in this process. However, how do the extracellular ROS produced by plasma transport into cells needs to be concerned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelsea et al . recently reported that using the plasma-activated air could deliver plasmid DNA into cells29, also suggesting that ROS are important for plasma transfection as the electric field is not involved in this process. However, how do the extracellular ROS produced by plasma transport into cells needs to be concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of its translation into major healthcare innovations include tissue ablation and coagulation, disinfection of food and living tissues, wound healing, and even cancer treatment23242526. Several groups have reported that plasma jet with pulsed high frequency could increase the cell permeability and delivery of GFP vectors in mammalian cells such as HeLa cells, CHL cells, Jurkat cells, Hacat cells and MCF-7 cells272829. Leduc et al .…”
mentioning
confidence: 99%
“…We previously reported the use of PAA for DNA transfer in vitro . 40 Initially, recellularized human dermal constructs were employed as an alternative delivery substrate before moving to an animal model. The recellularized dermal constructs provided a 3D structure more akin to human skin, and superior to existing in vitro skin models.…”
Section: Discussionmentioning
confidence: 99%
“…We previously confirmed the presence of ozone and NO 2 in the plasma-activated gas under operating parameters. 40 It is probable that the generation of diluted reactive species in the PAA assists plasmid DNA delivery. Both ozone and NO 2 effect cellular membranes, and the effects are enhanced with increasing product amounts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation